Preoperative binaural beats reduce remimazolam dosage and enhance safety in anesthesia induction: A randomized controlled trial - Hyun-Chang Kim; Jin Young Sohn; Myoung Hwa Kim; Yoon Jung Kim; Chul Ho Chang; Jeong-Hwa Seo (PLoS ONE, 2026)
Binaural beats, a form of auditory stimulation, are thought to reduce anxiety and anesthetic requirements through brainwave entrainment. Remimazolam offers advantages in terms of rapid onset and offset of action and hemodynamic stability. However, the optimal remimazolam dose for anesthesia induction remains unclear and there are concerns regarding variability in response and potential side effects at higher doses. This study investigated the effects of preoperative binaural beats on the remimazolam dose required for loss of consciousness during general anesthesia induction. In this randomized, prospective, single center study, 72 patients undergoing general anesthesia were allocated to two groups: the binaural sound (B group) or the control group. The B group listened to binaural sounds (1-Hz frequency difference) for 30 min preoperatively, while the control group did not. The B group required a significantly lower remimazolam dose for loss of consciousness (15.0 ± 3.6 vs. 17.7 ± 4.5 mg, p = 0.006) and achieved loss of consciousness faster (140 ± 29 vs. 168 ± 47 s, p = 0.003) than the control group. The incidence of hypotension was lower in the B group than in the control group (6 vs. 28%, p = 0.024). Electroencephalography spectral analysis revealed no significant between-group differences. Binaural beats significantly reduced the remimazolam dose required for loss of consciousness and shortened the time to loss of consciousness, while reducing the incidence of hypotension during anesthesia induction. Binaural beats are an effective, non-invasive method of enhancing efficiency and safety in anesthesia induction when using remimazolam infusion. Trial registration ClinicalTrials.gov NCT06099977